Homocysteine measurement in pig saliva, assay validation and changes after acute stress and experimental inflammation models: A pilot study. (June 2017) - Tecles, F.; Escribano, D.; Martínez-Miró, S.; Cerón, J.J.
Abstract: High homocysteine (Hcy) concentration in serum has been associated to stress and inflammation in humans, but this association has not been studied in saliva in any animal species. The purpose of this research was to study salivary Hcy levels in pigs under stressful and inflammatory conditions. A commercially available enzyme-linked immunosorbent assay specific for Hcy determination in pigs was adapted and validated in saliva, yielding reproducible and accurate results. Hcy was measured in paired serum-saliva samples and no correlation was observed between serum and salivary Hcy. Salivary Hcy was measured in two experimental models of stress induction in pigs: restraint with a nasal snare and isolation. Homocysteine concentration and the homocysteine to total protein (Hcy/TP) ratio significantly increased 15 min after restraining and decreased after some days of isolation. Significant correlation was observed between Hcy and chromogranin A. After an experimentally induced inflammation by subcutaneous turpentine injection, salivary Hcy increased only 3 h after turpentine administration; however, the Hcy/TP ratio did not show any change. No correlation was found between salivary Hcy and serum C-reactive protein. In conclusion, salivary Hcy concentration increased when pigs were restrained with a nasal snare or stressed by isolation, probably reflecting an increase in the sympathetic activity. On the other hand, Hcy increased after an experimental inflammation induced by turpentine administration but in this case probably reflects an increase in total protein production in saliva. Highlights: Homocysteine (Hcy) can be measured in pig saliva by a commercial ELISA assay. Hcy increased after restraint and isolation maybe due to sympathetic activity. Hcy significantly correlated to chromogranin A in saliva. Hcy rose after turpentine administration probably due to saliva concentration.